Development of Academic Supervision Instruments to Improve the Quality of Physical Education and Sports Learning and Health (Journal of Physical Education and Sports, 2018)
Improving teacher competencies, especially in paedagogic competencies need to be academic supervision with follow-up collegial dialogical coaching so that academic supervision has an important position in improving the quality of the learning process. The purpose of this study was to provide an alternative supervision instrument as a tool to observe student learning behavior and teach students to teachers, improve teacher skills in teaching students, which develops sustainably, thus impacting the development of student behavior, and the development of teacher creativity in finding alternative solutions to problems in school infrastructure. This research was conducted with the approach/method of development research (Research and Development), developing sports physical health and education learning supervision devices which included: preliminary studies, preparation of the initial draft of the instrument, expert validation for the initial draft, small scale trial (limited), revision product, broad-scale test (large), product revision of broad-scale test, and the formation of final product model for physical education learning supervision instrument. The results of the study showed that the supervision instruments for Physical Education in Primary Schools were developed from existing classroom supervision instruments. The instrument of supervision of development results consists of two instruments namely learning planning instruments and instruments for implementing learning. Each instrument consists of indicators that are clarified with descriptors as a guide to make it easier for supervisors to supervise.